2016
DOI: 10.1107/s2052520616003954
|View full text |Cite
|
Sign up to set email alerts
|

The Cambridge Structural Database

Abstract: The Cambridge Structural Database (CSD) contains a complete record of all published organic and metal-organic small-molecule crystal structures. The database has been in operation for over 50 years and continues to be the primary means of sharing structural chemistry data and knowledge across disciplines. As well as structures that are made public to support scientific articles, it includes many structures published directly as CSD Communications. All structures are processed both computationally and by expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

214
5,026
7
48

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 8,299 publications
(5,652 citation statements)
references
References 45 publications
214
5,026
7
48
Order By: Relevance
“…For all analyses we used CSD v.5.36 (November 2014; Allen, 2002; Groom et al , 2016) as the data source, and ConQuest v.1.15 was used for querying and retrieving data (Bruno et al , 2002). Apart from the normal pre-publication validation and refereeing processes, all data entering the CSD were carefully evaluated for chemical sense and for the internal consistency of coordinates, geometry, unit-cell parameters and space group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all analyses we used CSD v.5.36 (November 2014; Allen, 2002; Groom et al , 2016) as the data source, and ConQuest v.1.15 was used for querying and retrieving data (Bruno et al , 2002). Apart from the normal pre-publication validation and refereeing processes, all data entering the CSD were carefully evaluated for chemical sense and for the internal consistency of coordinates, geometry, unit-cell parameters and space group.…”
Section: Methodsmentioning
confidence: 99%
“…Following the initial publication of bond-valence parameters based on inorganic crystal structures (Brese & O’Keeffe, 1991; Brown & Altermatt, 1985), numerous studies have discussed the bond-valence model in the context of small-molecule crystal structures in the Cambridge Structural Database (CSD; Allen, 2002; Groom et al , 2016) as well as in the Inorganic Crystal Structure Database (ICSD; Bergerhoff & Brandenburg, 2004). Some notable results based on CSD data include bond-valence parameters for copper (Shields et al , 2000), lanthanides (Trzesowska et al , 2004, 2006), cadmium (Palenik, 2006), antimony (Palenik et al , 2005) and ammonium (García-Rodríguez et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have also been published reports on the coordination of metal cations with the carbonyl-or sulfonyl-oxygen of saccharin [5]; although the latter is less basic and is rarely involved in bonding. A comparatively rare (N,O)-bidentate bridging coordination mode, that is reported for one of the complexes in this study, has been found in only three examples in the literature [7,8,9].…”
Section: Introductionmentioning
confidence: 89%
“…74 SMILES strings are a non-unique representation which encode the molecular graph into a string of ASCII characters. SMILES strings for 56 of the Huang & Massa molecules were obtained from the Cambridge Structure Database Python API, 75 and the rest were generated by hand using a combination of the Optical Structure Recognition Application, 76 the www.molview.org molecule builder, and the Open Babel package 77 , which can convert .mol files to SMILES. Since Coulomb matrices require atomic coordinates, 3D coordinates for the molecules were generated using 2D→3D structure generation routines in the RDKit 53 and Open Babel 77 python packages.…”
Section: Data Gatheringmentioning
confidence: 99%